Opportunities and Challenges of the South Papua Railway Development Project: A Transportation Infrastructure Sustainability Perspective - Siti Aisyah; Ilham Sentosa (Westscience Press, 2023)
The South Papua Railway Development Project is an important effort to improve transportation connectivity in the region, which promises both opportunities and challenges from a sustainability perspective. This research methods paper adopts a mixed methods approach to comprehensively investigate the project's potential impacts on environmental, social, and economic sustainability. The findings reveal a complex landscape where economic growth and improved accessibility are juxtaposed with environmental concerns, community displacement, and cultural preservation challenges. To improve overall sustainability, recommendations include strong environmental mitigation, community engagement, cultural preservation, and effective cost management. This study underscores the need for a balanced development strategy that considers community welfare and ecosystem conservation, thus paving the way for responsible and sustainable infrastructure projects in South Papua.